A positive electrode material and a preparation method thereof and a battery
By using vinyl carbonate and vinyl carbonate as coating agents on the positive electrode materials of lithium-ion power batteries, the battery performance problems caused by manganese element dissolution is solved, the cycle and rate performance is significantly improved, and the battery life is extended .
Patent Information
- Application Number
- CN202311097328.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-29
AI Technical Summary
In the prior art, the modification of electrolyte cannot effectively improve the cycling performance and rate performance of lithium-ion power batteries, especially due to the electrode structure distortion and performance deterioration caused by the dissolution of manganese elements during charging and discharge.
Use substituted or unsubstituted vinyl carbonate and/or vinyl carbonate as coating agents to directly coat the surface of the positive electrode active material to form a protective film to inhibit the dissolution of manganese ions, and mix and heat coat through rotary evaporation process. Ensure uniform distribution and efficient adhesion of the coating agent.
The cycling performance and rate performance of the battery are significantly improved. By forming a uniform and dense protective film, the manganese ion dissolution is reduced, the positive electrode structure is stabilized, the battery life is extended and the polarization is reduced.
Smart Images

Figure BDA0004419552550000051 
Figure BDA0004419552550000121 
Figure BDA0004419552550000122
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a positive electrode material and a preparation method thereof, and a battery. Background Art
[0002] With the rapid development of new energy vehicles, lithium-ion power batteries have attracted more and more attention in the industry. Among them, the positive electrode material is a key factor in determining the electrical performance of lithium-ion power batteries. At present, the more successful commercial lithium-ion battery positive electrode materials in the industry mainly include layered cobalt oxide, ternary materials, spinel lithium manganese oxide and olivine lithium iron phosphate.
[0003] Among the many positive electrode materials for lithium-ion batteries, positive electrode materials containing manganese, such as lithium manganese oxide, spinel lithium nickel manganese oxide, layered lithium nickel manganese oxide, and lithium iron manganese phosphate, are low in price and are currently the focus of research in the industry.
[0004] In the above-mentioned positive electrode materials containing manganese, trivalent manganese ions have the Jan-Taylor effect during the battery charging and discharging process, which is easy to produce lattice distortion, and finally causes manganese to dissolve and deposit on the surface of the electrode material. Among them, when manganese dissolves and deposits on the surface of the positive electrode material, it will cause the positive electrode material to lack manganese phase, and hinder the diffusion of lithium ions in the subsequent charging and discharging process, and finally increase the polarization of the battery and cause serious capacity loss; when manganese dissolves and deposits on the surface of the negative electrode material, divalent manganese ions will diffuse into the negative electrode, and be reduced to a single substance from the surface to the inner layer, and then oxidized to divalent ions, and so on. The cycle is repeated, and at the same time, the amount of low-lithium embedded graphite in the negative electrode will increase, and the degree of disorder of the graphite surface will increase, and finally the SEI film on the surface of the negative electrode will be continuously destroyed and regenerated, consuming a large amount of active lithium and electrolyte solution, causing problems such as rapid attenuation of the battery life and gas production inside the battery.
[0005] In the related art, in order to overcome the problem of manganese ion dissolution, additives are usually added to the electrolyte to modify the electrolyte, and then the additives in the electrolyte are formed into a film on the surface of the positive electrode through a pre-charging formation process, thereby reducing the corrosion of the electrolyte on the surface of the positive electrode material and avoiding the collapse of the positive electrode material structure and deterioration of performance.
[0006] However, in the process of realizing the present invention, the inventors found that after the electrolyte was modified in the related art, the cycle performance and rate performance of the battery still need to be improved. Summary of the invention
[0007] In view of this, the present invention provides a positive electrode material and a preparation method thereof and a battery to solve the problem in the related art that modification of the electrolyte cannot effectively improve the cycle performance and rate performance of the battery.
[0008] In a first aspect, the present invention provides a positive electrode material, comprising: a positive electrode active substance and a coating layer coated on the surface of the positive electrode active substance, wherein the coating layer contains a coating agent, and the coating agent is selected from substituted or unsubstituted vinylene carbonate and / or substituted vinyl carbonate.
[0009] In the related art, ethylene carbonate, vinylene carbonate or analogs with similar structures are usually added to the electrolyte as additives and used to react and form a film on the electrode surface during the pre-charge formation process. However, there are usually a variety of additives in the electrolyte, and factors such as the reaction potential occurrence sequence, distribution concentration, distribution position and cross-linking reaction between various additives will affect the type and degree of film-forming reaction, that is, there is great uncertainty in the reaction sequence and degree of completion of various additives in the electrolyte, which will seriously affect the film-forming effect of the additives on the electrode surface, thereby resulting in poor cycle performance and rate performance of the battery.
[0010] In the above-mentioned positive electrode material provided by the present invention, substituted or unsubstituted vinylene carbonate and / or substituted ethylene carbonate are directly coated on the surface of the positive electrode active material as a coating agent. Compared with the case of adding to the electrolyte, on the one hand, these coating agents can form a protective film on the surface of the positive electrode active material by physical adsorption before chemical film formation; on the other hand, after the chemical film formation reaction begins, under the same film formation reaction conditions as in the electrolyte (e.g., under the same film formation triggering potential), the coating agent on the surface of the positive electrode active material in the positive electrode material is distributed more evenly, the concentration is also higher, and the reaction path gathered on the surface of the positive electrode active material is also shorter, and a film formation reaction can be quickly generated on the surface of the positive electrode active material to generate a uniform protective film, effectively inhibiting the dissolution of manganese ions, making the positive electrode structure more stable, and less manganese ions deposited on the negative electrode surface; and, the film formation reaction type is basically controllable, the reaction is more sufficient, the resulting protective film is more uniform, the thickness is thinner, the polarization is smaller, and the interface resistance is smaller. In this way, the cycle performance and rate performance of the battery are better.
[0011] In an optional embodiment, the substituted vinylene carbonate includes vinylene carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl, and the substituted vinyl carbonate includes vinyl carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl;
[0012] Optionally, the substituted vinylene carbonate includes at least one of 4,5-dimethyl-1,3-dioxol-2-one, 4-chloromethyl-5-methyl-1,3-dioxol-2-one, and 4-bromomethyl-5-methyl-1,3-dioxol-2-one;
[0013] Alternatively, the substituted ethylene carbonate comprises fluoroethylene carbonate.
[0014] In the above-mentioned positive electrode material provided by the present invention, the coating agent can form a film through free radical polymerization to form a dense and stable CEI film, which can effectively inhibit the dissolution of manganese ions and thus effectively avoid the deterioration of battery performance.
[0015] In an optional embodiment, the weight ratio of the coating agent to the positive electrode active material is (1-10):(100-2000).
[0016] In the positive electrode material provided by the present invention, the amount ratio of the coating agent to the positive electrode active material is appropriate, and the coating agent has a good coating effect on the positive electrode active material.
[0017] In an optional embodiment, the particle size D50 of the positive electrode active material is not greater than 40 μm, and the particle size D90 is not greater than 80 μm;
[0018] Optionally, the specific surface area of the positive electrode active material is not greater than 5m 2 / g.
[0019] In the positive electrode material provided by the present invention, the particle size of the positive electrode active material is appropriate, which is convenient for coating with the coating agent and effectively improves the coating effect, and can improve the battery performance on the other hand.
[0020] In an optional embodiment, the positive electrode active material includes a manganese-containing positive electrode material;
[0021] Optionally, the positive electrode active material includes at least one of lithium manganese oxide, spinel lithium nickel manganese oxide, layered lithium nickel manganese oxide, lithium iron manganese phosphate, lithium manganese phosphate, cobalt-free manganese-based lithium-rich material and nickel-cobalt-manganese ternary material.
[0022] In the positive electrode material provided by the present invention, the positive electrode active material has a wide range of sources, so that the positive electrode material has a wider application range.
[0023] In a second aspect, the present invention further provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0024] The coating agent and the organic solvent form a coating agent solution, and the coating agent solution is mixed with the positive electrode active material, and the mixture is rotary evaporated to perform mixing and heating coating.
[0025] In the above-mentioned preparation method provided by the present invention, the physical and chemical properties of the coating agent itself are taken into account, and mixed heating and coating are carried out by rotary evaporation, which can not only significantly improve the coating effect, but also has the advantages of simple process and low cost.
[0026] In an optional embodiment, the conditions for rotary evaporation include:
[0027] The water temperature of the rotary evaporator is 20°C to 150°C; the rotation speed is 20rpm to 100rpm; the vacuum degree is 90kpa to 96kpa; and the rotary evaporation is continued for 10min to 30min after the organic solvent is evaporated to dryness.
[0028] In an optional embodiment, the organic solvent includes at least one of ethanol, acetone, nitrogen methyl pyrrolidone, tetrahydrofuran, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, benzene, toluene, pentane, hexane, methanol, ether, carbon tetrachloride, styrene, tetrachloroethylene, trichloroethylene, ethylene glycol ether and triethanolamine.
[0029] In an optional embodiment, when the coating agent solution is mixed with the positive electrode active material, the amount of the coating agent and the amount of the positive electrode active material satisfy the following relationship:
[0030] m1 / m2=n×k×c×d×i×M1 / (10000×M2);
[0031] Wherein, m1 represents the amount of coating agent, in g;
[0032] M1 represents the molar molecular weight of the coating agent, in g / mol;
[0033] m2 represents the amount of positive electrode active material, in g;
[0034] M2 represents the molar molecular weight of the positive electrode active material, in g / mol;
[0035] n represents the stoichiometric ratio of Mn to Li in the positive electrode active material, and 0≤n≤1.95;
[0036] c represents the percentage value of the solid content of the coating agent solution, and 0 <c<11;
[0037] d represents the viscosity of the coating agent solution, in mPa.s, and 100≤d≤1950;
[0038] i represents the correction factor of the solid content of the coating agent solution, and 0.85 <i≤1.05;
[0039] k represents the addition coefficient of the coating agent, and 0 <k≤0.24。
[0040] In the above-mentioned preparation method provided by the present invention, after determining the amount of the coating agent and the solid content and viscosity of the solution according to the above formula, during the rotary evaporation process, the coating agent can be evenly heated so that it can be well dispersed in the organic solvent. After the rotary evaporation is completed, part of the organic solvent is evaporated, and the remaining organic solvent can assist the coating agent to be evenly coated on the surface of the positive electrode active material, thereby enhancing the adhesion of the coating agent on the surface of the positive electrode active material, which can significantly reduce the difficulty of rotary evaporation coating and improve the coating effect.
[0041] In a third aspect, the present invention further provides a battery comprising the above-mentioned positive electrode material. DETAILED DESCRIPTION
[0042] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0043] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0044] In order to solve the problems existing in the above-mentioned related technologies, according to the first aspect of the present invention, a positive electrode material is provided, including: a positive electrode active material and a coating layer coated on the surface of the positive electrode active material, the coating layer contains a coating agent, and the coating agent is selected from substituted or unsubstituted vinylene carbonate and / or substituted vinyl carbonate.
[0045] In the above-mentioned positive electrode material provided by the present invention, substituted or unsubstituted vinylene carbonate and / or substituted ethylene carbonate are directly coated on the surface of the positive electrode active material as a coating agent. Compared with the case of adding to the electrolyte, on the one hand, these coating agents can form a protective film on the surface of the positive electrode active material by physical adsorption before chemical film formation; on the other hand, after the chemical film formation reaction begins, under the same film formation reaction conditions as in the electrolyte (e.g., under the same film formation triggering potential), the coating agent on the surface of the positive electrode active material in the positive electrode material is distributed more evenly, the concentration is also higher, and the reaction path gathered on the surface of the positive electrode active material is also shorter, and a film formation reaction can be quickly generated on the surface of the positive electrode active material to generate a uniform protective film, effectively inhibiting the dissolution of manganese ions, making the positive electrode structure more stable, and less manganese ions deposited on the negative electrode surface; and, the film formation reaction type is basically controllable, the reaction is more sufficient, the resulting protective film is more uniform, the thickness is thinner, the polarization is smaller, and the interface resistance is smaller. In this way, the cycle performance and rate performance of the battery are better.
[0046] In an optional embodiment, the substituted vinylene carbonate includes vinylene carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl, and the substituted vinyl carbonate includes vinyl carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl;
[0047] Optionally, the substituted vinylene carbonate includes at least one of 4,5-dimethyl-1,3-dioxol-2-one, 4-chloromethyl-5-methyl-1,3-dioxol-2-one, and 4-bromomethyl-5-methyl-1,3-dioxol-2-one;
[0048] Alternatively, the substituted ethylene carbonate comprises fluoroethylene carbonate.
[0049] Among them, the structural formula of fluoroethylene carbonate is shown in formula A, the structural formula of 4,5-dimethyl-1,3-dioxol-2-one is shown in formula B, the structural formula of 4-chloromethyl-5-methyl-1,3-dioxol-2-one is shown in formula C, and the structural formula of 4-bromomethyl-5-methyl-1,3-dioxol-2-one is shown in formula D.
[0050]
[0051] In the above-mentioned positive electrode material provided by the present invention, the coating agent can form a film through free radical polymerization to form a dense and stable CEI film, which can effectively inhibit the dissolution of manganese ions and thus effectively avoid the deterioration of battery performance.
[0052] In an optional embodiment, the weight ratio of the coating agent to the positive electrode active material is (1-10):(100-2000).
[0053] In the positive electrode material provided by the present invention, the amount ratio of the coating agent to the positive electrode active material is appropriate, and the coating agent has a good coating effect on the positive electrode active material.
[0054] In an optional embodiment, the particle size D50 of the positive electrode active material is not greater than 40 μm, and the particle size D90 is not greater than 80 μm;
[0055] Optionally, the specific surface area of the positive electrode active material is not greater than 5m 2 / g.
[0056] In the positive electrode material provided by the present invention, the particle size of the positive electrode active material is appropriate, which is convenient for coating with the coating agent and effectively improves the coating effect, and can improve the battery performance on the other hand.
[0057] In an optional embodiment, the positive electrode active material includes a manganese-containing positive electrode material;
[0058] Optionally, the positive electrode active material includes at least one of lithium manganese oxide, spinel nickel lithium manganese oxide, layered nickel lithium manganese oxide, lithium iron manganese phosphate, lithium manganese phosphate, cobalt-free manganese-based lithium-rich material and nickel-cobalt-manganese ternary material. Among them, the nickel-cobalt-manganese ternary material can be, for example, NCM523, NCM622, NCM613, NCM55, NCM721, NCM811, NCM9055. In another optional embodiment, the positive electrode active material can also be NCA material and LFP material.
[0059] In the positive electrode material provided by the present invention, the positive electrode active material has a wide range of sources, so that the positive electrode material has a wider application range.
[0060] In a second aspect, the present invention further provides a method for preparing the above-mentioned positive electrode material, comprising the following steps:
[0061] The coating agent and the organic solvent form a coating agent solution, and the coating agent solution is mixed with the positive electrode active material, and the mixture is rotary evaporated to perform mixing and heating coating.
[0062] In the above-mentioned preparation method provided by the present invention, the physical and chemical properties of the coating agent itself are taken into account, and mixed heating and coating are carried out by rotary evaporation, which can not only significantly improve the coating effect, but also has the advantages of simple process and low cost.
[0063] In an optional embodiment, the conditions for rotary evaporation include:
[0064] The water temperature of the rotary evaporator is 20℃~150℃; the rotation speed is 20rpm~100rpm; the vacuum degree is 90kpa~96kpa; the rotary evaporation is continued for 10min~30min after the organic solvent is evaporated to dryness. In addition, the rotary evaporation time can also be set to 30min~240min.
[0065] In a preferred embodiment, the conditions for rotary evaporation include: water temperature of 100° C., rotation speed of 80 rpm, time of 40 min, vacuum degree of 90 kPa, and rotary evaporation for 20 min at a temperature-keeping rate after the organic solvent is evaporated to dryness.
[0066] In an optional embodiment, the organic solvent includes at least one of ethanol, acetone, nitrogen methyl pyrrolidone, tetrahydrofuran, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, benzene, toluene, pentane, hexane, methanol, ether, carbon tetrachloride, styrene, tetrachloroethylene, trichloroethylene, ethylene glycol ether and triethanolamine.
[0067] In an optional embodiment, when the coating agent solution is mixed with the positive electrode active material, the amount of the coating agent and the amount of the positive electrode active material satisfy the following relationship:
[0068] m1 / m2=n×k×c×d×i×M1 / (10000×M2);
[0069] Wherein, m1 represents the amount of coating agent, in g;
[0070] M1 represents the molar molecular weight of the coating agent, in g / mol;
[0071] m2 represents the amount of positive electrode active material, in g;
[0072] M2 represents the molar molecular weight of the positive electrode active material, in g / mol;
[0073] n represents the stoichiometric ratio of Mn to Li in the positive electrode active material, and 0≤n≤1.95;
[0074] c represents the percentage value of the solid content of the coating agent solution, and 0 <c<11;
[0075] d represents the viscosity of the coating agent solution, in mPa.s, and 100≤d≤1950;
[0076] i represents the correction factor of the solid content of the coating agent solution, and 0.85 <i≤1.05;
[0077] k represents the addition coefficient of the coating agent, and 0 <k≤0.24。
[0078] In the above-mentioned preparation method provided by the present invention, after determining the amount of the coating agent and the solid content and viscosity of the solution according to the above formula, during the rotary evaporation process, the coating agent can be evenly heated so that it can be well dispersed in the organic solvent. After the rotary evaporation is completed, part of the organic solvent is evaporated, and the remaining organic solvent can assist the coating agent to be evenly coated on the surface of the positive electrode active material, thereby enhancing the adhesion of the coating agent on the surface of the positive electrode active material, which can significantly reduce the difficulty of rotary evaporation coating and improve the coating effect.
[0079] In a third aspect, the present invention further provides a battery comprising the above-mentioned positive electrode material.
[0080] The present invention is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed by the present invention.
[0081] Example 1
[0082] Prepare the positive electrode material as follows:
[0083] (1) dissolving 2 g of vinylene carbonate in 38 g of ethanol, heating and maintaining the temperature at 35° C., and then stirring until completely dissolved to obtain a coating agent solution;
[0084] Wherein, the solid content of the coating agent solution is 5wt% and the viscosity is 1000mPa.s;
[0085] (2) Lithium iron manganese phosphate powder (LiMn 0.6 Fe 0.4 PO4-LMFP) through a 500-mesh sieve, and 100 g of the sieved lithium manganese iron phosphate powder is mixed with 40 g of the coating agent solution prepared in step (1) to obtain a mixed material;
[0086] Among them, in the sieved lithium manganese iron phosphate powder, the particle size D50 of lithium manganese iron phosphate is 0.8μm, the particle size D90 is 11.8μm, and the specific surface area is 3.4m 2 / g;
[0087] In this step, the amount of coating agent (vinylene carbonate) m1 = 2g, the molar molecular weight of coating agent (vinylene carbonate) M1 = 86.05g / mol, the amount of positive active material (lithium manganese iron phosphate) m2 = 100g, the molar molecular weight of positive active material (lithium manganese iron phosphate) M2 = 157.2g / mol, the stoichiometric ratio of Mn to Li in the positive active material (lithium manganese iron phosphate) n = 3:5 = 0.6, the solid content of coating agent solution c = 5.0 wt%, viscosity value of coating agent solution d=1000mPa.s, correction coefficient of solid content of coating agent solution i=1.015, addition coefficient of coating agent (vinylene carbonate) k=0.12, m1 / m2=2 / 100=0.02, n×k×c×d×i×M1 / (10000×M2)=3 / 5×0.12×5.0×1000×1.015×86.05 / (10000×157.2)=0.02;
[0088] (3) The mixed material obtained in step (2) is added to a rotary evaporator for mixing, heating and coating, wherein the water temperature of the rotary evaporator is set to 100° C., the rotation speed is set to 80 rpm, the rotation time is 40 min, and the vacuum degree is 90 kPa. After the ethanol is evaporated to dryness, the rotary evaporation is maintained at the temperature for 20 min to obtain vinylene carbonate-coated lithium manganese iron phosphate powder, which is the positive electrode material prepared in this embodiment.
[0089] Example 2
[0090] A positive electrode material was prepared according to the method of Example 1, except that in step (1) of this example, 2.465 g of fluoroethylene carbonate was used to replace 2 g of vinylene carbonate, and the solid content of the obtained coating agent solution was 6.1 wt % and the viscosity was 1000 mPa.s;
[0091] In step (2) of this embodiment, the amount of coating agent (fluoroethylene carbonate) m1=2.465g, the molar molecular weight of coating agent (fluoroethylene carbonate) M1=106.05g / mol, the amount of positive electrode active material (lithium manganese iron phosphate) m2=100g, the molar molecular weight of positive electrode active material (lithium manganese iron phosphate) M2=157.2g / mol, the stoichiometric ratio of Mn to Li in the positive electrode active material (lithium manganese iron phosphate) n=3:5=0.6, the solid content of coating agent solution c=6.1w t%, viscosity value of coating agent solution d = 1000mPa.s, correction coefficient of solid content of coating agent solution i = 0.99, addition coefficient of coating agent (fluoroethylene carbonate) k = 0.1008, m1 / m2 = 2.465 / 100 = 0.02465, n×k×c×d×i×M1 / (10000×M2) = 3 / 5×0.1008×6.1×0.99×1000×106.05 / (10000×157.2) = 0.02465.
[0092] Example 3
[0093] The positive electrode material was prepared according to the method of Example 1, except that in step (1) of this example, 2.652 g of 4,5-dimethyl-1,3-dioxol-2-one was used to replace 2 g of vinylene carbonate, and the solid content of the obtained coating agent solution was 6.52 wt % and the viscosity was 1096 mPa.s;
[0094] In step (2) of this embodiment, the amount of coating agent (4,5-dimethyl-1,3-dioxol-2-one) is m1=2.652 g, the molar molecular weight of coating agent (4,5-dimethyl-1,3-dioxol-2-one) is M1=114.1 g / mol, the amount of positive electrode active material (lithium manganese iron phosphate) is m2=100 g, the molar molecular weight of positive electrode active material (lithium manganese iron phosphate) is M2=157.2 g / mol, the stoichiometric ratio of Mn to Li in the positive electrode active material (lithium manganese iron phosphate) is n=3 / 5=0.6, and the solid content of coating agent solution is The amount c = 6.52, the viscosity value of the coating agent solution d = 1096 mPa.s, the correction coefficient of the solid content of the coating agent solution i = 0.97, the addition coefficient k of the coating agent (4,5-dimethyl-1,3-dioxol-2-one) = 0.08785, m1 / m2 = 2.652 / 100 = 0.02652, n×k×c×d×i×M1 / (10000×M2) = 3 / 5×0.08785×6.52×1096×0.97×114.1 / (10000×157.2) = 0.02652.
[0095] Example 4
[0096] The positive electrode material was prepared according to the method of Example 1, except that in step (1) of this example, 3.452 g of 4-chloromethyl-5-methyl-1,3-dioxol-2-one was used to replace 2 g of vinylene carbonate, and the solid content of the obtained coating agent solution was 8.32 wt % and the viscosity was 1137 mPa.s;
[0097] In step (2) of this embodiment, the amount of coating agent (4-chloromethyl-5-methyl-1,3-dioxol-2-one) is m1=3.452 g, the molar molecular weight of coating agent (4-chloromethyl-5-methyl-1,3-dioxol-2-one) is M1=148.54 g / mol, the amount of positive electrode active material (lithium manganese iron phosphate) is m2=100 g, the molar molecular weight of positive electrode active material (lithium manganese iron phosphate) is M2=157.2 g / mol, the stoichiometric ratio of Mn to Li in the positive electrode active material (lithium manganese iron phosphate) is n=3 / 5=0.6, and the solid content of coating agent solution is 1.347 g / mol. The amount c = 8.32wt%, the viscosity value of the coating agent solution d = 1137mPa.s, the correction coefficient of the solid content of the coating agent solution i = 0.97, the addition coefficient k of the coating agent (4-chloromethyl-5-methyl-1,3-dioxol-2-one) = 0.06635, m1 / m2 = 3.452 / 100 = 0.03452, n×k×c×d×i×M1 / (10000×M2) = 3 / 5×0.06635×8.32×1137×0.97×148.54 / (10000×157.2) = 0.03452.
[0098] Example 5
[0099] The positive electrode material was prepared according to the method of Example 1, except that in step (1) of this example, 4.485 g of 4-bromomethyl-5-methyl-1,3-dioxol-2-one was used to replace 2 g of vinylene carbonate, and the solid content of the obtained coating agent solution was 10.56 wt % and the viscosity was 1750 mPa.s;
[0100] In step (2) of this embodiment, the amount of coating agent (4-bromomethyl-5-methyl-1,3-dioxol-2-one) is m1=4.485 g, the molar molecular weight of coating agent (4-bromomethyl-5-methyl-1,3-dioxol-2-one) is M1=193 g / mol, the amount of positive electrode active material (lithium manganese iron phosphate) is m2=100 g, the molar molecular weight of positive electrode active material (lithium manganese iron phosphate) is M2=157.2 g / mol, the stoichiometric ratio of Mn to Li in the positive electrode active material (lithium manganese iron phosphate) is n=3 / 5=0.6, and the solid content of coating agent solution is c = 10.56wt%, viscosity value of coating agent solution d = 1750mPa.s, correction coefficient of solid content of coating agent solution i = 0.95, addition coefficient of coating agent (4-bromomethyl-5-methyl-1,3-dioxol-2-one) k = 0.03468, m1 / m2 = 4.485 / 100 = 0.04485, n×k×c×d×i×M1 / (10000×M2) = 3 / 5×0.03468×10.56×1750×0.95×193 / (10000×157.2) = 0.04485.
[0101] Example 6
[0102] The positive electrode material was prepared according to the method of Example 1, except that in step (2) of this embodiment, the lithium manganese iron phosphate powder was sieved through a 300-mesh sieve. In the sieved lithium manganese iron phosphate powder, the particle size D50 of the lithium manganese iron phosphate was 18 μm, the particle size D90 was 78 μm, and the specific surface area was 1.9 m 2 / g.
[0103] Example 7
[0104] The positive electrode material was prepared according to the method of Example 1, except that in step (3) of this example, the water temperature of the rotary evaporator was set to 120°C, the rotation speed was set to 60 rpm, the rotation time was 25 min, the vacuum degree was 96 kPa, and after the ethanol was evaporated, the rotary evaporation was kept warm for 15 min.
[0105] Comparative Example 1
[0106] The positive electrode material was prepared according to the method of Example 1, except that in step (1) of this comparative example, 2.05 g of ethylene carbonate was used to replace 2 g of vinylene carbonate, and the solid content of the obtained coating agent solution was 5.12 wt % and the viscosity was 1024 mPa.s;
[0107] In step (2) of this comparative example, the amount of coating agent (ethylene carbonate) m1=2.05g, the molar molecular weight of coating agent (ethylene carbonate) M1=88.06g / mol, the amount of positive electrode active material (lithium manganese iron phosphate) m2=100g, the molar molecular weight of positive electrode active material (lithium manganese iron phosphate) M2=157.2g / mol, the stoichiometric ratio of Mn to Li in the positive electrode active material (lithium manganese iron phosphate) n=3 / 5=0.6, the solid content of coating agent solution c=5.12w t%, viscosity value of coating agent solution d = 1024mPa.s, correction coefficient of solid content of coating agent solution i = 0.95, addition coefficient of coating agent (ethylene carbonate) k = 0.1225, m1 / m2 = 2.05 / 100 = 0.0205, n×k×c×d×i×M1 / (10000×M2) = 3 / 5×0.1225×5.12×1024×0.95×88.06 / (10000×157.2) = 0.0205.
[0108] Preparation Example
[0109] (1) Using the positive electrode materials prepared in Examples 1 to 7 and Comparative Example 1 in sequence, button batteries S1 to S7 and D1 were prepared according to the following method:
[0110] The slurry was homogenized according to the weight ratio of positive electrode material: conductive agent SP: binder PVDF = 92:4:4, and the obtained slurry was coated on the positive electrode collector (aluminum foil) and dried to obtain a positive electrode sheet with a compaction density of 2.2 g / cm 3 ; A 600μm thick lithium sheet is used as the negative electrode sheet; the electrolyte is: EC:DMC:PC=1:1:1, 1.5MliPF6; the separator is: 9 (base film) + 3 (ceramic boehmite) + 1 (PVDF) + 1 (PVDF) um PE; assembled into a 2032 button battery and packaged.
[0111] (2) Using the lithium manganese iron phosphate powder that passed through a 500-mesh sieve in step (2) of Example 1 as the positive electrode material, a button cell D2 was prepared according to the following method:
[0112] The slurry was homogenized according to the weight ratio of positive electrode material: conductive agent SP: binder PVDF = 92:4:4, and the obtained slurry was coated on the positive electrode collector (aluminum foil) and dried to obtain a positive electrode sheet with a compaction density of 2.2 g / cm 3 ; A 600μm thick lithium sheet is used as the negative electrode sheet; the electrolyte is: EC:DMC:PC=1:1:1, 1.5MliPF6; the separator is: 9 (base film) + 3 (ceramic boehmite) + 1 (PVDF) + 1 (PVDF) um PE; assembled into a 2032 button battery and packaged.
[0113] (3) Using the lithium manganese iron phosphate powder passed through a 500-mesh sieve in step (2) of Example 1 as the positive electrode material, a button cell D3 was prepared according to the following method:
[0114] The slurry was homogenized according to the weight ratio of positive electrode material: conductive agent SP: binder PVDF = 92:4:4, and the obtained slurry was coated on the positive electrode collector (aluminum foil) and dried to obtain a positive electrode sheet with a compaction density of 2.2 g / cm 3 ; A 600μm thick lithium sheet is used as the negative electrode sheet; the electrolyte is: EC:DMC:PC=1:1:1, 1.5MliPF6, 1% volume of vinyl carbonate; the separator is: 9 (base film) + 3 (ceramic boehmite) + 1 (PVDF) + 1 (PVDF) um PE; assembled into a 2032 button battery and packaged.
[0115] Experimental example
[0116] (1) Perform EIS test on each button cell according to the following method:
[0117] ① After the fourth cycle of low current formation at 0.5C, the test was started on the electrochemical workstation while maintaining 50% SOC;
[0118] ②Imperature measurement was performed immediately after cycling at a potential amplitude of 5 mV in the frequency range of 100 KHz to 10 mHz. The results are shown in Table 1.
[0119] (2) Perform ICP element test on each button battery according to the following method:
[0120] ① In the range of 2.0V-4.4V, first use constant current CC+CV, that is, first use constant current 0.1C, then constant voltage 4.3V until the current is less than 0.02C, change to 1.0CC / 1.0CD after 2 cycles, and remove the button after 50 cycles;
[0121] ② Disassemble the button battery, remove the lithium metal negative electrode, and rinse it repeatedly with DMC solvent for 3 times to remove the lithium salt and solvent on the surface;
[0122] ③ Place the lithium sheet rinsed in step ② into 50 mL of a 4% dilute nitric acid solution for digestion to obtain a digested solution;
[0123] ④ The digested solution was subjected to ICP injection test to obtain the corresponding element results. The results are shown in Table 2.
[0124] Table 1 EIS test results of each button battery
[0125]
[0126] Table 2 ICP test results of button batteries
[0127]
[0128] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The positive electrode material comprises: a positive electrode active material and a coating layer coated on the surface of the positive electrode active material, wherein the coating layer contains a coating agent, and the coating agent is selected from substituted or unsubstituted vinylene carbonate and / or substituted vinyl carbonate; the preparation method of the positive electrode material comprises the following steps: The coating agent and an organic solvent form a coating agent solution, and the coating agent solution is mixed with the positive electrode active material, and rotary evaporation is performed to perform mixed heating coating. When the coating agent solution is mixed with the positive electrode active material, the amount of the coating agent and the amount of the positive electrode active material satisfy the following relationship: m1 / m2=n×k×c×d×i×M1 / (10000×M2); Wherein, m1 represents the amount of the coating agent, in g; M1 represents the molar molecular weight of the coating agent, in g / mol; m2 represents the amount of the positive electrode active material, in g; M2 represents the molar molecular weight of the positive electrode active material, in g / mol; n represents the stoichiometric ratio of Mn to Li in the positive electrode active material, and 0≤n≤1.95; c represents the percentage value of the solid content of the coating agent solution, and 0 <c<11; d represents the viscosity of the coating agent solution, in mPa.s, and 100≤d≤1950; i represents the correction coefficient of the solid content of the coating agent solution, and 0.85 <i≤1.05; k represents the addition coefficient of the coating agent, and 0 <k≤0.24。 2. The method for preparing the positive electrode material according to claim 1, characterized in that: The substituted vinylene carbonate includes vinylene carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl, and the substituted vinyl carbonate includes vinyl carbonate substituted at the 4-position and / or the 5-position by at least one of halogen, methyl or halomethyl.
3. The method for preparing the positive electrode material according to claim 2, characterized in that: The substituted vinylene carbonate includes at least one of 4,5-dimethyl-1,3-dioxol-2-one, 4-chloromethyl-5-methyl-1,3-dioxol-2-one, and 4-bromomethyl-5-methyl-1,3-dioxol-2-one.
4. The method for preparing the positive electrode material according to claim 1, characterized in that: The substituted ethylene carbonate includes fluoroethylene carbonate.
5. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The weight ratio of the coating agent to the positive electrode active material is (1-10): (100-2000).
6. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The particle size D50 of the positive electrode active material is not greater than 40 μm, and the particle size D90 is not greater than 80 μm.
7. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The specific surface area of the positive electrode active material is not greater than 5 m 2 / g.
8. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The positive electrode active material includes a manganese-containing positive electrode material.
9. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The positive electrode active material includes at least one of lithium manganese oxide, spinel lithium nickel manganese oxide, layered lithium nickel manganese oxide, lithium iron manganese phosphate, lithium manganese phosphate, cobalt-free manganese-based lithium-rich material and nickel-cobalt-manganese ternary material.
10. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The conditions of the rotary evaporation include: The water temperature of the rotary evaporator is 20°C to 150°C; the rotation speed is 20 rpm to 100 rpm; the vacuum degree is 90 kPa to 96 kPa; and the rotary evaporation is continued for 10 min to 30 min after the organic solvent is evaporated to dryness.
11. The method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The organic solvent includes at least one of ethanol, acetone, nitrogen methyl pyrrolidone, tetrahydrofuran, ethyl acetate, N,N-dimethylformamide, N,N-dimethylacetamide, benzene, toluene, pentane, hexane, methanol, ether, carbon tetrachloride, styrene, tetrachloroethylene, trichloroethylene, ethylene glycol ether and triethanolamine. 12 . The positive electrode material obtained by the method for preparing a positive electrode material according to claim 1 .
13. A battery, characterized in that: The battery contains the positive electrode material according to claim 12.
